Enterococcus Faecalis CECT712: biopreservation of crafted goat cheese - Sparo, Mónica Delfina (2012)
Poor hygienic practices along manufacture process may result in bacterial contamination of craft cheese. The aim of this work was to assess the biopreservative activity of the probiotic strain Enterococcus faecalis CECT7121 on the indigenous microbiota in crafted goat cheese. A goat milk mixture was divided in two groups: Group A, not inoc ulated with the probiotic strain and Group B, inoculated with E. faecalis CECT7121 (5.0 x 104 CFU.mL-1). Small farms` traditional protocol for cheese manufacturing was followed. Viable cell counts of Lactobacillus spp., Lactococcusspp., Enterococcus spp.,Enterobacteriaceae and Staphylococcus aureus were performed. Presence of the probiotic strain in group B was determined by Pulsed-Field Gel Electrophoresis technique. Viable cell counts at T=0 and at the end of the experiment, T=35 days, for the assessment of E. faecalis CECT7121 inhibitory activity were carried out. Bactericidal activity of E. faecalis CECT7121 against Enterobacteriaceae and S. aureus was proven. However, viable cell counts of Lactobacillus spp. and Lactococcuswere spp. were not modified. The biopreservative activity shown by the probiotic strain E. faecalis CECT7121 should be considered as a potential tool for a safer craft goat cheese manufacture.